Faktor-Faktor Dominan Kualitas Pelayanan Pramusaji Yang Mempengaruhi Kepuasan Tamu Di Restoran Pondok Bebek, Hotel Arbor Biz - Anggun Sari Sasmita; Nila Sartika Achmadi; Rafika Hayati (Akademi Pariwisata Bunda Mulia, 2019)
ABSTRACT This study describes the dominant factors in the quality of waiter service that affect guest satisfaction at Pondok Bebek Restaurant. Data collection uses a questionnaire that measures the five dimensions of waiter service quality which consists of tangibles, reliability, responsiveness, assurance, and empathy dimensions to 86 duck cottage restaurant guests. Data obtained from the questionnaire results were processed by determining the average value. The results of this study indicate the five variables of guest satisfaction greatly influence the satisfaction of guests in the duck cottage restaurant. Whereas the most dominant factor affecting guest satisfaction in this restaurant is Responsiveness or responsiveness with a value of 992. The results of the first indicator which is providing information about food promos are at a score of 329, the second indicator is an explanation of the menu at a score of 336, the third indicator is employees able to answer questions about restaurants is at a score of 327.Keywords: Restaurant, Service quality, Guest satisfaction. ABSTRAK Penelitian ini menguraikan faktor dominan kualitas pelayanan pramusaji yang mempengaruhi kepuasan tamu pada Restoran Pondok Bebek. Pengumpulan data menggunakan angket yang mengukur dengan lima dimensi kualitas pelayanan pramusajiyang terdiri atas dimensi tangibles, reliability, responsiveness, assurance, dan empathy kepada 86 tamu restoran pondok bebek. Data yang didapatkan dari hasil angket diolah dengan menentukan nilai rata-rata.. Hasil dari penelitian ini menunjukkan kelima variabel kepuasan tamu sangat berpengaruh terhadap kepuasan tamu di restoran pondok bebek. Sedangkan faktor yang berpengaruh paling dominan terhadap kepuasan tamu di restoran ini adalah Responsiveness atau daya tanggap dengan nilai 992. Hasil indikator pertama yaitu memberikan informasi mengenai promo makanan berada pada skor 329, indikator kedua yaitu penjelasan mengenai menu berada pada skor 336, indikator ketiga yaitu karyawan mampu menjawab pertanyaan mengenai restoran berada pada skor 327.Kata kunci: Restoran, Kualitas pelayanan, Kepuasan tamu